Development of Analytical Method for Predicting Residual Mechanical Properties of Corroded Steel Plates. (23rd June 2011) - Appuhamy, J. M. R. S.; Ohga, M.; Kaita, T.; Fujii, K.; Dissanayake, P. B. R.
Abstract : Bridge infrastructure maintenance and assurance of adequate safety is of paramount importance in transportation engineering and maintenance management industry. Corrosion causes strength deterioration, leading to impairment of its operation and progressive weakening of the structure. Since the actual corroded surfaces are different from each other, only experimental approach is not enough to estimate the remaining strength of corroded members. However, in modern practices, numerical simulation is being used to replace the time-consuming and expensive experimental work and to comprehend on the lack of knowledge on mechanical behavior, stress distribution, ultimate behavior, and so on. This paper presents the nonlinear FEM analyses results of many corroded steel plates and compares them with their respective tensile coupon tests. Further, the feasibility of establishing an accurate analytical methodology to predict the residual strength capacities of a corroded steel member with lesser number of measuring points is also discussed.